Health and Well-Being Among Elderly - Ankita Singh,; Dr. Suvidha, (International Journal of Scientific Research in Science and Technology, 2024)
The world's population is aging rapidly; by 2025, the elderly, or anyone over 60, are expected to account for 22% of the total population. Even though older adults participate in fewer regenerative activities, the rise in age-related illnesses and impairments puts them at greater risk. This has a number of detrimental social and economic effects on individuals as well as society at large. Methods: A review of the literature was done in the light of these potential problems to locate empirical studies assessing the health and well-being of senior citizens. Results: Empirical data retrieved from multiple studies indicates that seniors who live outside of institutions have higher levels of emotional well-being than those who live in them. This is because the former has access to better medical care, social connections, family care, and financial independence. Older adults without substantial financial resources experience abuse, are left behind, and are no longer included in family decision-making or selection procedures. For this subset of the population, spiritual care is recommended. It follows that seniors should continue exercising and participating in physical activity at the recommended level.
Keywords: Well-being; Elderly; Senior Citizens; Older Adults; Physical Activity